Effects of mobile app on memory retention of vocabulary knowledge among low proficiency EFL learners - Dan, Cao; Ismail, Lilliati; Razali, Abu Bakar (Canadian Center of Science and Education, 2024)
A significant challenge in EFL vocabulary learning is ensuring long-term retention and effective use of newly acquired words, often hindered by limited exposure and meaningful practice. Considerable research has been conducted on mobile technologies for vocabulary learning in a second language (L2), but the comprehensive mastery of EFL vocabulary form, meaning, and use via mobile platforms in short-term and long-term memory has rarely been addressed. This quasi-experimental study investigated the effects of a mobile vocabulary app versus a paper-based wordlist on high-frequency core vocabulary from CET 4 among Chinese university students. Data were collected from 82 EFL freshmen at a private university in China from two intact groups. The experimental group used the Bai Cizhan app for out-of-classroom learning, while the control group used traditional paper-based methods. Vocabulary knowledge was tested through pretests, immediate recall tests, and delayed recall post-tests. Findings indicated that Bai Cizhan group significantly enhanced L2 vocabulary learning in improving high-frequency core words vocabulary in terms of form and meaning (Form: F (1, 80) = 23.957, p < .05, η2 = .230; Meaning: F (1, 80) = 16.342, p < .05, η2 = .170) in short-term memory, but no significant difference (Wilks’ Lambda=.187, F(3, 78)=1.641; P>.05) in long-term memory. This study provides empirical evidence for the effectiveness of mobile-assisted vocabulary learning and offers insights into meeting the vocabulary needs of EFL learners.